The competition between metastable and equilibrium S (Al2CuMg) phase during the decomposition of AlCuMg alloys. (1st October 2015) - Styles, M.J.; Marceau, R.K.W.; Bastow, T.J.; Brand, H.E.A.; Gibson, M.A.; Hutchinson, C.R.
Abstract: The decomposition sequence of the supersaturated solid solution leading to the formation of the equilibrium S (Al2 CuMg) phase in AlCuMg alloys has long been the subject of ambiguity and debate. Recent high-resolution synchrotron powder diffraction experiments have shown that the decomposition sequence does involve a metastable variant of the S phase (denoted S1), which has lattice parameters that are distinctly different to those of the equilibrium S phase (denoted S2). In this paper, the difference between these two phases is resolved using high-resolution synchrotron and neutron powder diffraction and atom probe tomography, and the transformation from S1 to S2 is characterised in detail by in situ synchrotron powder diffraction. The results of these experiments confirm that there are no significant differences between the crystal structures of S1 and S2, however, the powder diffraction and atom probe measurements both indicate that the S1 phase forms with a slight deficiency in Cu. The in situ isothermal aging experiments show that S1 forms rapidly, reaching its maximum concentration in only a few minutes at high temperatures, while complete conversion to the S2 phase can take thousands of hours at low temperature. The kinetics of S phase precipitation have been quantitatively analysed for the first time and it is shown that S1 phase forms with an average activation energy of 75 kJ/mol, which is much lower than the activation energy for Cu and Mg diffusion in an Al matrix (136 kJ/mol and 131 kJ/mol, respectively). The mechanism of the replacement of S1 with the equilibrium S2 phase is discussed.